The reliability and validity of the Patient Health Questionnaire-9 (PHQ-9) and PHQ-2 in patients with infertility - Saman Maroufizadeh; Reza Omani-Samani; Amir Almasi-Hashiani; Payam Amini; Mahdi Sepidarkish (Reproductive Health, 2019)
Abstract Background Depression in patients with infertility often goes undiagnosed and untreated. The Patient Health Questionnaire-9 (PHQ-9) and its ultra-brief version (i.e. PHQ-2) are widely used measures of depressive symptoms. These scales have not been validated in patients with infertility. The aim of the present study was to examine the reliability and validity of the PHQ-9 and PHQ-2 in patients with infertility. Methods In this cross-sectional study, a total of 539 patients with infertility from a referral infertility clinic in Tehran, Iran completed the PHQ-9, along with other relevant scales: the WHO-five Well-being Index (WHO-5), the Hospital Anxiety and Depression Scale (HADS), and the Generalized Anxiety Disorder-7 (GAD-7). Factor structure and internal consistency of PHQ-9 were examined via confirmatory factor analysis (CFA) and Cronbach’s alpha, respectively. Convergent validity was evaluated by relationship with WHO-5, HADS and GAD-7. Results The mean total PHQ-9 and PHQ-2 scores were 8.47 ± 6.17 and 2.42 ± 1.86, respectively, and using a cut-off value of 10 (for PHQ-9) and 3 (for PHQ-2), the prevalence of depressive symptoms was 38.6 and 43.6%, respectively. The Cronbach’s alphas for PHQ-9 and PHQ-2 were, respectively, 0.851 and 0.767, indicating good internal consistency. The CFA results confirmed the one-factor model of the PHQ-9 (χ2/df = 4.29; CFI = 0.98; RMSEA = 0.078 and SRMR = 0.044). Both PHQ-9 and PHQ-2 showed moderate to strong correlation with the measures of WHO-5, HADS-depression, HADS-anxiety, and the GAD-7, confirming convergent validity. In univariate analysis, female sex, long infertility duration, and unsuccessful treatment were significantly associated with depression symptoms. Conclusion Both PHQ-9 and PHQ-2 are brief and easy to use measures of depressive symptoms with good psychometric properties that appear suitable for routine use in patients with infertility.